Tools Matter: Mediated Writing Activity in Alternative Digital Environments. - Ching, Kory Lawson (Written Communication, 2018)
This study examines the experiences and perceptions of writers who composed text using “distraction-free” writing tools that stand as alternatives to standard word processing programs. The purpose of this research was to develop a clearer understanding of how digital writing tools may shape the activities and practices of writers, as well as what writing with unfamiliar tools and technologies might reveal about writing processes. Analysis of study participants’ reflective narratives of their composing experience suggests the extent to which writing tools and technologies influence routine practices, assist writers as they try to direct their attention (and avoid distraction), motivate writing, and impact writers’ “text sense” as they compose. Moreover, findings indicate how different tools and technologies may be viewed as more or less useful for different writing tasks. This article ends with a call for writing researchers, writing teachers, and software developers to attend more critically to the ways writing technologies shape the practices of writers.